Jiawei Shengmai San herbal formula ameliorates diabetic associate cognitive decline by modulating AKT and CREB in rats. (3rd July 2020) - Ahmed, Ayaz; Zeng, Guirong; Azhar, Mudassar; Lin, Haiying; Zhang, Mijia; Wang, Fengzhong; Zhang, Hong; Jiang, Dejian; Yang, Sijin; Farooq, Ahsana Dar; Choudhary, Muhammad Iqbal; Liu, Xinmin; et al.
Abstract : Memory loss is a complication of diabetes which requires new approaches to its treatment. Shengmai San (SMS) is a famous traditional Chinese formula containing Panax ginseng, Ophiopogon japonicas, and Schisandra chinensis, whereas Radix puerariae has many reported pharmacological uses. In this study the combination, as Jiawei SMS (J‐SMS) was screened for its ability to reverse diabetes‐associated cognitive decline in rats. This was assessed behaviorally in diabetic rats (Streptozotocin, 45 mg/kg), with biochemical and western blot analysis (Akt and CREB). Diabetic rats showed fasting blood glucose (FBG) in the range of 13–15 mM throughout the study. J‐SMS (0.5, 1.5, 4.5 g/kg) treatment significantly improved learning and memory deficit among diabetic rats as evidenced by preference for novel object, reduced escape latency and increased number of platform crossings ( p < .05) in the NORT and MWM tests. Treatment with J‐SMS also significantly improved the histopathological changes in the diabetic brain and increased the protein expression of AKT and CREB, required for proper memory function ( p < .01). This study highlighted that J‐SMS can reverse reference and working memory deficit among diabetic rats by modulating AKT and CREB proteins activation. Thus, J‐SMS formulation might be possible candidate for further development. Highlights: The herbal formula Shengmai San and Radix puerariae (J‐SMS) in combination reversed diabetes‐associated cognitive decline in diabetic rats. Diabetic rats showed impaired learning and memory in Morris water maze test (MWM), novel object recognition test (NORT) with histopathological changes and downregulation protein expression of AKT, CREB in the brain. After J‐SMS treatment, the diabetic rats showed reduced escape latency and enhanced platform crossing number in MWM, enhanced tendency to explore new objects in NORT, improved the histopathological changes and upregulated protein expression of AKT, CREB in the brain.